Ultra-Low-Profile Wideband Magneto-Electric Dipole Antenna - Wang, Heesu; Park, Ikmo (Proceedings of the IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, APWC, 2024)
Recently, as wireless communication technology has gradually advanced, the demand for antennas with wideband characteristics continues to increase. Dipole antennas are widely used because they can implement wideband characteristics with a simple structure, and various types of dipole antennas have been presented. Magneto-electric dipole antennas have a directional radiation pattern with a wide bandwidth. Due to these advantages, they are suitable for various wireless communication applications that require broadband and high gain characteristics [1]. However, conventional magneto-electric dipole antennas have a high profile close to 0.25 λ0, where λ0 is the center frequency of operating bandwidth. Therefore, their application to wireless communication devices is limited. For this reason, various studies have been conducted to reduce the profile of magneto-electric dipole antennas. To reduce the profile of the antenna, the antennas using a bent magnetic dipole were widely used. The antennas using bent magnetic dipoles can achieve a lower profile than antennas with straight magnetic dipoles. However, there are limits to significantly reducing the profile of the antenna.
Keywords: Broadband gain; Directional radiation; Low-profile; Magneto-electric dipole antennas; Simple structures; Wide bandwidth; Wide-band; Wideband characteristics; Wireless communication applications; Wireless communication technology